EFEKTIFITAS MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI MAN SIPIROK - Parsautan Harahap; Anni Holila (JURNAL MathEdu (Mathematic Education Journal), 2018)
student facilitator and explaining learning model and students’ mathematical problem solving ability